ACSS2 upregulation enhances neuronal resilience to aging and tau-associated neurodegeneration - Naemeh Pourshafie; Desi C. Alexander; Hong Xu; Kechun Yang; Greg Donahue; Xue Lei; Shuo Zhang; Oksana Shcherbakova; Connor Hogan; Michael Gilbert; Kevt’her Hoxha; Lesley Chaboub; et al. (Proceedings of the National Academy of Sciences, 2026)
Epigenetic mechanisms, including histone acetylation, regulate learning and memory and underlie Alzheimer’s disease and related dementia (ADRD). Acetyl-CoA synthetase 2 (ACSS2), an enzyme generating acetyl-CoA, locally regulates histone acetylation and gene expression in neuronal nuclei. This regulatory mechanism may be a promising target for therapeutic intervention in neurodegenerative diseases. Previously, we showed that systemic ACSS2 knockout mice, although largely normal in physiology, exhibit memory deficits. Here, we investigated whether increasing ACSS2 levels could protect neurons against disease and age-associated cognitive decline. Given the role of tau in ADRD, we used primary hippocampal neurons that mimic the sporadic development of tau pathology and the P301S transgenic mouse model for tau-induced memory decline. Our results show that ACSS2 upregulation mitigates tau-induced transcriptional alterations, enhances neuronal resilience against tau pathology, improves long-term potentiation, and ameliorates memory deficits. Additionally, boosting histone acetylation through ACSS2 countered age-related memory decline. These findings indicate that increasing ACSS2 is highly effective in countering age- and tau-induced transcriptome changes, preserving elevated levels of synaptic genes, and safeguarding synaptic integrity. These findings position ACSS2 as a key epigenetic regulator of cognitive aging and ADRD, highlighting its potential for targeted therapeutics to enhance brain resilience and function.